Risk of Shallot Supply Chain: An Analytical Hierarchy Process (AHP) Model in Brebes Java, Indonesia - Susanawati Susanawati; Muhammad Fauzan (International Journal of Supply Chain Management, 2019)
This study aimed to determine actors and to identify the types of risk in the shallot supply chain. It was conducted in Central Java, Indonesia, involving an expert from goverment representatives, academician, and actors of thechain as the respondents. Descriptive analysis was used to describe actors of chain.To identify risk of the chain,the AHP model was applied. The results showed that farmers, middlemen, businessmen, consignors, big-scale merchants, traders, retailers, and consumers are the actors of the chain. Meanwhile, the price risk played the most important one in the chain, followed by quality risk and market risk.